Water Crisis and Its Relation to Achieving Sustainable Agricultural Development in Iraq (The Real Causes and Proposed Solutions) - حسين, محمد بدوي; بشير, كامل كاظم; حسون, رسول هادي (Journal of Economics and Administrative Sciences, 2019)
The conservation of natural resources such as water is one of the areas that sustainable agriculture seeks to preserve, rationalize its use and protect it from pollution, because water is a specific factor for agriculture. Despite Iraq's possession of two international rivers, the Tigris and the Euphrates, which pour into the Shatt Al-Arab, it suffers from water shortages in recent times, As a result of several reasons combined, including water policies initiated by the riparian countries to reduce the quantities of water coming from the two rivers to Iraq, led by neighbor Turkey through the construction of dams and reservoirs and the establishment of irrigation projects, as well as climate changes from rising temperatures and low fall rate that Iraq falls within Arid and semi-arid areas, and the increasing demand for water in all the magazines, including agriculture as a result of the increase in population, water problem has become a water crisis worsens over time, which affected the process of agricultural production and the delay of achieving sustainable agricultural development, as there is an inverse relationship between them and the water crisis, In order to solve this problem, it is necessary to know the real causes of the crisis and find solutions and appropriate treatment, The researcher concluded that the nature of the water problem is that the water supply is less than the demand for it, and to solve this problem is either increase the water offered in exchange for demand or reduce the demand for the amount offered. The study proposed a set of solutions, including the formation of a high committee for water management in Iraq, which will prepare strategic water plans and spread modern irrigation techniques throughout Iraq, and resort to supplementary irrigation such as the use of water harvesting and the construction of dams and reservoirs after the identification of actual water needs and the establishment of educational awareness campaigns for producers and ideas on holding talks with riparian countries to increase the levels of the Tigris and Euphrates River according to economic policies that satisfy all parties. The research reached some conclusions, including that the degree of the causes of the crisis The most severe of which is poor water management and the lack of integrated management